Między biologią a teologią: człowiek - Hałaczek, Bernard (Śląskie Studia Historyczno-Teologiczne, 2000)
There is an essential difference between the biological (empirical) and theological description of a man. Originating from asking different questions, this difference results in different explanations. A biologist explains a man in terms of his past considering his position in the evolutionary development of life. A theologist, in turn, explains a man in the context of future and asks questions concerning the aim of his existence in the World created by God. The ignorance of the above differences was the reason of a conflict between natural and theological concepts of the formation of the first human being. In view of the Bible description of Man, the theologists were definitely against the evolutionary interpretation of the human origin. On the other hand, in view of the theory of evolution, the biologists negated the creation of the first Man. The theologists talking about the „how” of human appearance attempted to answer biological questions, while the philosophical theological problems were discussed by the biologists, whose interest was focused on the questions of human „what” and „who”. The fault of both consisted of an attempt for totally explaining the Man within one epistemological platform. The conflict between biology and theology became less serious after confining methodological reflection of these two branches of science to the subject and limits of their cognition. Biology did not attempt to find full explanation of the origins of all essential human features any more, whilst theology did not try to develop more precise description the „how” of human origin. The conflict definitely disappeared as soon as biologists and theologists agreed that their research programmes are not unique and that the correct description of Man requires a simultaneous development of both or even more programmes.